2016
DOI: 10.1038/srep34339
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective Effects of 7, 8-dihydroxyflavone on Midbrain Dopaminergic Neurons in MPP+-treated Monkeys

Abstract: Parkinson’s disease (PD) is one common neurodegenerative disease caused by a significant loss of midbrain dopaminergic neurons. Previous reports showed that 7, 8- dihydroxyflavone (7, 8-DHF) as a potent TrkB agonist can mimic BDNF and play neuroprotective roles for mouse dopaminergic neurons. Nonetheless, the safety and neuroprotective effects are unclear in monkey models of PD. Here, we find that 7, 8-DHF could be absorbed and metabolized into 7-hydroxy-8-methoxyflavone through oral administration in monkeys.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…These findings are in agreement with recent studies that have also identified flavone, catechin and ellagic acid as the major phenolic compounds in feijoa fruit [5,6,40]. It has been reported that 7,8-dihydroxyflavone exerts strong neuroprotective effects in monkeys [41], is effective in early brain trauma recovery in male rats [42], and has potential anticancer activity [40]. However, further studies on the potential health benefits of feijoa fruit in humans and the exact mode of action of its bioactive compounds are warranted.…”
Section: Resultssupporting
confidence: 92%
“…These findings are in agreement with recent studies that have also identified flavone, catechin and ellagic acid as the major phenolic compounds in feijoa fruit [5,6,40]. It has been reported that 7,8-dihydroxyflavone exerts strong neuroprotective effects in monkeys [41], is effective in early brain trauma recovery in male rats [42], and has potential anticancer activity [40]. However, further studies on the potential health benefits of feijoa fruit in humans and the exact mode of action of its bioactive compounds are warranted.…”
Section: Resultssupporting
confidence: 92%
“…Moreover, according to the results from in vivo pharmacokinetic studies in mice, DHF efficiently penetrates the brain after oral administration (50 mg/Kg), showing a brain to plasma concentration ratio of approximately 1:1 and an elimination half-life of about 2 hours 83 . However, an even longer half-life of 4–8 hours was measured in primate plasma after oral administration (30 mg/Kg) 150 . Although DHF has been shown to activate TrkB in the brain after acute administration 85 , 86 , we failed to detect any increase in TrkB phosphorylation in both WT and Ts65Dn mice after a single dose.…”
Section: Discussionmentioning
confidence: 99%
“…Although the action of TrkB receptor signalling is important for optimal neuronal function [20], the poor pharmacokinetic of BDNF [21] has limited the pharmacological implementation of BDNF to treat neurological disorders. The TrkB signalling cascade possesses the therapeutic potential to limit TBI pathology by critically linking energy metabolism and plasticity.…”
Section: Discussionmentioning
confidence: 99%